KELAYAKAN PENERAPAN INTRODUKSI TEKNOLOGI MODEL TANAM GANDA (DOUBLE RAW) JAGUNG-KACANG TANAH PADA LAHAN KERING DI KABUPATEN MUNA BARAT - Fyka, Samsul Alam (Universitas Islam Madura, 2023)
The double cropping model (double raw) for peanut corn is the introduction of technology applied by farmers to maximize land potential and increase farmers' income. The purpose of this study was to determine the feasibility of applying the technology introduction of the double cropping model (double raw) of peanut corn on dry land in West Muna Regency. The research method used in this research is qualitative and quantitative research. The number of respondents was 44 people, with details of 22 people with double planting and 22 people with monoculture. The analytical tool used in this research is benefit cost ratio (MBCR) analysis. The results showed that the income of farmers applying the double cropping model (double raw) was greater, namely IDR3.285.386/ha/MT compared to the monoculture model, which was IDR1.108.485/ha/MT. As a result of applying the double cropping model (double raw) there is an excess of production costs of IDR 537,389/ha/MT, compared to maize monoculture. However, there was an excess of revenue, amounting to IDR 2.714.290/ha/MT. So that the results of the MBCR analysis are 5.05. This means that for each additional input in the double raw corn – peanut cropping pattern of IDR1.000, it will increase income by IDR5.050.